Comprehensive cancer predisposition testing within the prospective MASTER trial identifies hereditary cancer patients and supports treatment decisions for rare cancers - Jahn, Arne; Rump, A.; Widmann, T. J.; Heining, C.; Horak, Peter; Hutter, Barbara; Paramasivam, Nagarajan; Uhrig, Sebastian; Gieldon, Laura; Drukewitz, S.; Kübler, A.; Bermudez, M.; et al. (Annals of oncology, 2022)
Background - Germline variant evaluation in precision oncology opens new paths toward the identification of patients with genetic tumor risk syndromes and the exploration of therapeutic relevance. Here, we present the results of germline variant analysis and their clinical implications in a precision oncology study for patients with predominantly rare cancers. - Patients and methods - Matched tumor and control genome/exome and RNA sequencing was carried out for 1485 patients with rare cancers (79%) and/or young adults (77% younger than 51 years) in the National Center for Tumor Diseases/German Cancer Consortium (NCT/DKTK) Molecularly Aided Stratification for Tumor Eradication Research (MASTER) trial, a German multicenter, prospective, observational precision oncology study. Clinical and therapeutic relevance of prospective pathogenic germline variant (PGV) evaluation was analyzed and compared to other precision oncology studies. - Results - Ten percent of patients (n = 157) harbored PGVs in 35 genes associated with autosomal dominant cancer predisposition, whereof up to 75% were unknown before study participation. Another 5% of patients (n = 75) were heterozygous carriers for recessive genetic tumor risk syndromes. Particularly, high PGV yields were found in patients with gastrointestinal stromal tumors (GISTs) (28%, n = 11/40), and more specifically in wild-type GISTs (50%, n = 10/20), leiomyosarcomas (21%, n = 19/89), and hepatopancreaticobiliary cancers (16%, n = 16/97). Forty-five percent of PGVs (n = 100/221) supported treatment recommendations, and its implementation led to a clinical benefit in 40% of patients (n = 10/25). A comparison of different precision oncology studies revealed variable PGV yields and considerable differences in germline variant analysis workflows. We therefore propose a detailed workflow for germline variant evaluation. - Conclusions - Genetic germline testing in patients with rare cancers can identify the very first patient in a hereditary cancer family and can lead to clinical benefit in a broad range of entities. Its routine implementation in precision oncology accompanied by the harmonization of germline variant evaluation workflows will increase clinical benefit and boost research.